Prescription opioid dispensing and prescription opioid poisoning: Population data from Victoria, Australia 2006 to 2013 - Janneke Berecki‐Gisolf; Behrooz Hassani‐Mahmooei; Angela Clapperton; Roderick McClure (Elsevier, 2017)
Abstract Objective: To describe recent trends in opioid prescribing and prescription opioid poisoning resulting in hospitalisation or death in Victoria, Australia. Method: This is a population‐based ecological study of residents of Victoria, 2006 - 14. Australian Bureau of Statistics residential population data were combined with Pharmaceutical Benefits Scheme (PBS) opioid prescription data, Victorian Admitted Episodes Data (VAED) and cause of death data. Results: Annual opioid dispensings increased by 78% in 2006 - 13, from 0.33 to 0.58 per population. Opioid use increased with age: in 2013, 14% of Victorian residents aged ≥65 years filled at least one oxycodone prescription. In 2006 - 14, prescription opioid related hospital admissions increased by 6.8% per year, from 107 to 187 /1,000,000 person‐years; 56% were due to intentional self‐poisoning. Annual deaths increased from 21 to 28 /1,000,000 persons, in 2007 - 11. Admissions and deaths peaked at 25-44 years. Conclusions: Although both opioid prescribing and poisoning have increased, there is discrepancy between the exposed group (dispensings increased with age) and those with adverse consequences (rates peaked at ages 25-44 years). Implications: A better understanding is needed of drivers of prescribing and adverse consequences. Together with monitoring of prescribing and poisoning, this will facilitate early detection and prevention of a public health problem.